From influenza to COVID-19: Lipid nanoparticle mRNA vaccines at the frontiers of infectious diseases. (1st September 2021) - Pilkington, Emily H.; Suys, Estelle J.A.; Trevaskis, Natalie L.; Wheatley, Adam K.; Zukancic, Danijela; Algarni, Azizah; Al-Wassiti, Hareth; Davis, Thomas P.; Pouton, Colin W.; Kent, Stephen J.; Truong, Nghia P.
Abstract: Vaccination represents the best line of defense against infectious diseases and is crucial in curtailing pandemic spread of emerging pathogens to which a population has limited immunity. In recent years, mRNA vaccines have been proposed as the new frontier in vaccination, owing to their facile and rapid development while providing a safer alternative to traditional vaccine technologies such as live or attenuated viruses. Recent breakthroughs in mRNA vaccination have been through formulation with lipid nanoparticles (LNPs), which provide both protection and enhanced delivery of mRNA vaccines in vivo . In this review, current paradigms and state-of-the-art in mRNA-LNP vaccine development are explored through first highlighting advantages posed by mRNA vaccines, establishing LNPs as a biocompatible delivery system, and finally exploring the use of mRNA-LNP vaccines in vivo against infectious disease towards translation to the clinic. Furthermore, we highlight the progress of mRNA-LNP vaccine candidates against COVID-19 currently in clinical trials, with the current status and approval timelines, before discussing their future outlook and challenges that need to be overcome towards establishing mRNA-LNPs as next-generation vaccines. Statement of significance: With the recent success of mRNA vaccines developed by Moderna and BioNTech/Pfizer against COVID-19, mRNA technology and lipid nanoparticles (LNP) have never received more attention. This manuscript timely reviews the most advanced mRNA-LNP vaccines that have just been approved for emergency use and are in clinical trials, with a focus on the remarkable development of several COVID-19 vaccines, faster than any other vaccine in history. We aim to give a comprehensive introduction of mRNA and LNP technology to the field of biomaterials science and increase accessibility to readers with a new interest in mRNA-LNP vaccines. We also highlight current limitations and future outlook of the mRNA vaccine technology that need further efforts of biomaterials scientists to address. Graphical abstract: Image, graphical abstract